Avascular necrosis of the humeral head following bilateral upper extremity vascular composite allotransplantation: a case report. Issue 1 (1st January 2017) - Rinkinen, Jacob; Molway, David; Carty, Matthew; Dyer, George S. M.; Pomahac, Bohdan; Chandraker, Anil; Talbot, Simon G.
Abstract: Vascularised composite allotransplantation (VCA) represents an exciting and emerging field in plastic and reconstructive surgery. Despite the generally good functional and psychosocial outcomes, multiple complications can be associated with the procedure. The authors describe a case of avascular necrosis of the humeral head following successful upper extremity VCA.